Touchy : A Visual Approach for Simulating Haptic Effects on Touchscreens - Costes, Antoine; Argelaguet, Ferran; Danieau, Fabien; Guillotel, Philippe; Lécuyer, Anatole (Frontiers in ICT, 2019)
Haptic enhancement of touchscreens usually involves vibrating motors producing limited sensations or custom mechanical actuators that are difficult to disseminate. In this paper, we propose an alternative approach called “Touchy,” where a symbolic cursor is introduced under the user's finger, to evoke various haptic properties through changes in its shape and motion. This novel metaphor enables to address four different perceptual dimensions, namely: hardness, friction, fine roughness, and macro roughness. Our metaphor comes with a set of seven visual effects that we compared with real texture samples within a user study conducted with 14 participants. Taken together our results show that Touchy is able to elicit clear and distinct haptic properties: stiffness, roughness, reliefs, stickiness, and slipperiness.